Protective Effect of Luffa cylindrica L. Fruit in Paracetamol Induced Hepatotoxicity in Rats - Balakrishnan, N. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT In present study to evaluate the hepatoprotective activity of the ethanol and aqueous extracts (100 and 200 mg/kg) of fruit of Luffa cylindrica were studied on paracetamol (2 gm/kg) treated albino rats. The hepatoprotective effect was evaluated on the basis of various biochemical parameters which includes aspartate aminotransferase (AST) and alanine aminotransferase (ALT),serum alkaline phosphatise(ALP), total bilirubin (TB), total cholesterol (TC) and total protein (TP). Treatment with ethanol and aqueous extracts (100 and 200 mg/kg) of fruit of Luffa cylindrical shown significant hepatoprotective effect and also supported by histopathological study.